Analysis Characteristics of Arabic Language Elementary School Exam Questions - Bahy, Moh. Buny Andaru; Hidayanti, Primasti Nur Yusrin (Al-Ahruf (Journal for Arabic and Linguistics Education), 2023)
Evaluation in the form of a test is one of the most important elements that is usually used in a learning process, so educators should know the level of difficulty and the differentiating power of the items made. Therefore, this study was written to determine the level of difficulty and discriminating power of Arabic language test items in the final semester assessment of class V at Khairunnas Elementary School, Surabaya. This study uses a literature-based quantitative descriptive approach. The main data in this study are Arabic questions at the Final Assessment of the Arabic Semester at Khairunnas Elementary School, Surabaya. Based on the research that has been carried out, the researchers found that: The researcher found: (1) The difficulty level of the multiplechoice questions was that there were 2 (10%) difficult questions, 16 (80%) moderate questions, and 2 (10%) easy questions. Meanwhile, the difficulty level of the short description questions is: 1 difficult category (10%), 8 medium categories (80%), and 1 easy category (10%). at the difficulty level of the long description questions, 0 items were found in the difficult category (0%), 3 moderate questions (60%), and 2 easy questions (40%). (2) Multiple choice questions on the discriminating power of the items found that 2 items (10%) were in very good category, 9 items (45%) were good, 7 items (35%) were sufficient, and 2 items (10%) were bad. Furthermore, in the question of brief descriptions obtained items in the very good category 1 item (10%), good 4 items (40%), enough 1 item (10%) and 3 items (30%) poor category. As well as on the discriminating power of long description items, 3 items (60%) are in very good category, 0 items (0%) are good, 0 items (0%) are sufficient, and 2 items (40%) are bad. Referensi Al Fathiyah, S. F. (2019). Analisis Butir Soal Pelajaran Bahasa Arab Di MA Roudlotul Ulum Pagak Malang. Tarbiyatuna: Jurnal Pendidikan Ilmiah, 4(1), 76–100. Elis Ratna Wulan, E., & Rusdiana, A. (2015). Evaluasi pembelajaran. Pustaka Setia. Fatimah, L. U., & Alfath, K. (2019). Analisis Kesukaran Soal, Daya Pembeda dan Fungsi Distraktor. Al-Manar, 8(2), 37–64. https://doi.org/https://doi.org/10.36668/jal.v8i2.115 Fikriyah, N. (2021). Analisis Butir Soal Ulangan Tengah Semester Mata Pelajaran Bahasa Arab Kelas VII Semester Ganjil SMP Muhammadiyah 1 Yogyakarta Tahun Ajaran 2019/2020. Maharaat: Jurnal Pendidikan Bahasa Arab, 3(2), 128–140. https://doi.org/https://doi.org/10.18196/mht.v3i2.10501 Hanifah, N. (2017). Perbandingan Tingkat Kesukaran, Daya Pembeda Butir Soal Dan Reliabilitas Tes Bentuk Pilihan Ganda Biasa Dan Pilihan Ganda Asosiasi Mata Pelajaran Ekonomi. Sosio E-KONS, 6(1). https://doi.org/http://dx.doi.org/10.30998/sosioekons.v6i1.1715 Moleong, L. J. (2012). Metode Penelitian Kualitatif dan Kuantitatif. Remaja Rosdakarya, Bandung. Nuriyah, N. (2016). Evaluasi pembelajaran: sebuah kajian teori. Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 3(1). Primaningtyas, M., & Edi Setyawan, C. (2019). Urgensi Bahasa Arab dalam Pendidikn Islam di Era Revolusi Industri 4.0. Jurnal Saliha, 2(2). Suharsimi, A. (2006). Prosedur penelitian suatu pendekatan praktik. Jakarta: Rineka Cipta, 120–123. Wibawa, E. A. (2019). Karakteristik butir soal tes ujian akhir semester hukum bisnis. Jurnal Pendidikan Akuntansi Indonesia, 17(1), 86–96.